Personality Traits, Loneliness, and Affect Among Boxers - Chen, Xin; Qiu, Nan; Chen, Chao; Zhai, Liang (Frontiers in Psychology, 2021)
This study was aimed to test the association between personality traits and affect, and to figure out whether loneliness mediated this relationship.This study used The Big Five Personality Traits Scale, The UCLA Loneliness Scale, and The PANAS Scales were administered to N = Two hundred and thirty-one boxers (age: M = 20.28; SD = 2.60), of which 62% were male (n = 144) and 38% were female (n = 87). The results showed that (1) conscientiousness, extraversion, and agreeableness were negatively related with negative affect, neuroticism was positively associated with negative affect, openness showed no relationship with negative affect; (2) conscientiousness, extraversion, and agreeableness were all positively correlated with positive affect, neuroticism was negatively associated with positive affect，openness showed no relationship with positive affect; (3) conscientiousness, extraversion, openness, and agreeableness were negatively related with loneliness, neuroticism was positively associated with loneliness;(4) loneliness was positively associated negative affect, loneliness was negatively associated with positive affect; loneliness had mediating effect on the relationship between the personality traits and affect. Furthermore, these ﬁndings suggest that loneliness might be one mechanism explaining how boxer’s personality traits inﬂuence their affect. Therefore, in the future, we can start from helping them reduce their loneliness to reduce their negative affect, and improve their positive affect. And, also in the way, we can help them improve their sport performance and mental health．